Geniposide and Chlorogenic Acid Combination Ameliorates Non-alcoholic Steatohepatitis Involving the Protection on the Gut Barrier Function in Mouse Induced by High-Fat Diet - Peng, Jing-hua; Leng, Jing; Tian, Hua-jie; Yang, Tao; Fang, Yi; Feng, Qin; Zhao, Yu; Hu, Yi-yang (Frontiers in Pharmacology, 2018)
Gut-liver axis is increasingly recognized to be involved in the pathogenesis and progression of non-alcoholic fatty liver disease (NAFLD). The gut microbiota and intestinal permeability have been demonstrated to be the key players in the gut-liver cross talk in NAFLD. Geniposide and chlorogenic acid (GC) combination is derived from a traditional Chinese medicine, Qushi Huayu Decoction (QHD), which has been used in clinic for NAFLD treatment for decades in China and validated in multiple animal models of NAFLD. GC combination previously has been demonstrated to treat NAFLD via modulation on the gut microbiota composition. In the present study, the effects of GC combination on gut barrier function in NAFLD were evaluated, and QHD and sodium butyrate (NaB), the intestinal mucosa protectant, were used as positive control. The therapeutic effect of GC combination on NAFLD were confirmed by amelioration on non-alcoholic steatohepatitis (NASH) induced by high-fat diet (HFD) in mouse, which was comparable to that of QHD. Simultaneously, GC combination was found to reduce the signaling of gut-derived lipopolysaccharide (LPS) including hepatic LPS binding protein, Toll like receptor 4, interleukin-1β, tumor necrosis factor -α and Kupffer cells infiltration. Furthermore, GC combination reduced LPS and D-lactate in plasma, restoring the colonic tight junction (TJ) expression and inhibited colonic TJs disassembly by down-regulation on RhoA / ROCK signaling in NASH induced by HFD. On the other hand, NASH was also alleviated in NaB group. The results of the present study suggested the important role of protection on gut barrier function in NAFLD treatment, which contributed to the therapeutic effects of GC combination on NASH.